Peran Media Koran Mandala dalam Fungsi Watchdog Pers sebagai Bagian dari Civil Society di Kota Bandung - Angelina Qur’ainny (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the role of Koran Mandala as a local newspaper in performing the press watchdog function as part of civil society in Bandung City. This research is significant because existing studies on watchdog journalism in Indonesia have predominantly focused on national media, while the role of local newspapers in monitoring power and shaping democratic public spaces remains underexplored. Using qualitative descriptive method with a case study approach, data were collected through in-depth interviews with journalists and editors, observation of news production practices, and document analysis of investigative reports and opinion articles published by Koran Mandala between 2022 and 2024. The findings indicate that Koran Mandala plays a substantial watchdog role by critically reporting on local governance, alleged corruption, and public policies that directly affect citizens. Such investigative coverage contributes to public opinion formation, enhances civic awareness, and strengthens local government accountability. This study highlights the strategic importance of local media in reinforcing democratic values and the role of civil society at the municipal level.